A novel remote‐controlled robotic system for cerebrovascular intervention. Issue 6 (30th July 2018) - Shen, Hao; Wang, Cheng; Xie, Le; Zhou, Shoujun; Gu, Lixu; Xie, Hongzhi
Abstract: Background: In cerebrovascular intervention (CVI), the use of robots has considerable advantages over conventional surgery. This study introduces a remote‐controlled robotic system, including the first in vivo proof‐of‐concept trial. Methods: The robotic system uses a master–slave control strategy. Omega 3 was selected as the master manipulator, and the slave side executed the procedure of inserting the guidewire and balloon catheter, and angiography. The first in vivo trial was conducted to test whether the guidewire could be successfully moved from a pig's femoral artery to its carotid artery using our robotic system. Results: The insertion of the guidewire and balloon catheter and the angiography were successfully accomplished without any vascular rupture. The guidewire was successfully inserted into the secondary branches of the pig's carotid. The robot‐assisted surgery took a little more time than manual surgery. Conclusions: The successful first in vivo trial indicates the feasibility and effectiveness of the robotic system.